Developing knowledge community: What is beyond n-helix? - Yanuar Nugroho (Proceedings of AICS - Social Sciences, 2017)
Perhaps one most important signifier of progress in this age is knowledge creation. Today, knowledge has become the basic substance and fabric of the whole dynamics of the society. Knowledge sector has given birth to what we now know as knowledge-based economy, knowledge-based society, knowledge-based policymaking and politics, and even knowledge-based culture. However, scholarly debate on knowledge creation seems to have somehow reached saturation point. ‘Triple-helix’ (Etzkowitz Leydesdorff, 2000) was coined, after the ‘New Production of Knowledge’ (Gibbons, 1994), in an effort to understand the dynamics of the interaction among different actors –government, universities, and business—in fostering innovation, technological progress, and knowledge transfer (Etzkowitz Leydesdorff, 2000:118). Quickly becoming a ‘norm’ in innovation policy (after Lundvall, Borras, 2005) many started to follow with quadruple, quintuple, sextuple, and more, helices. Yet, at the conceptual level, there is nothing new after ‘triple helix’: that knowledge has never been created and produced monolithically, let alone in a centralised manner. Knowledge production is always multidimensional, distributed, and involves multi-actors. In many economies, particularly the emerging ones like Indonesia, knowledge is perceived to be significantly helping inform policy and development. But what are actually the implications of this to policymaking processes? To what extent do knowledge inform policy and how? This presentation attempts to provide some insights on the matter by focusing on the way in which knowledge has been advanced to inform development policy.